2019
DOI: 10.24853/elif.1.2.81-88
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Errors Analysis on Students’ Synopsis Writing

Abstract: The objective of the study is to find out the students’ morphological errors in synopsis writing. It aimed to know what the difficulty is faced by the students in their synopsis writing. The methodology of study is a qualitative that focused to analyze the students’ synopsis writing errors. The research finding is found that several students have synopsis writing errors in some aspects refer to omission, misordering, misinformation, and addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This happens as the result of the natural language learning process where the foreign language learner tries to apply the target language and results in several deviations on the target language (Rahimi & Tafazoli, 2014;Sawalmeh, 2013). The target language deviation is caused by incomplete learning, in which the students do not fully comprehend the target language construction (Guo, 2021;Rahman, 2019). Even though it is a common phenomenon, ignoring the errors may lead the students to perceive the error fossilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This happens as the result of the natural language learning process where the foreign language learner tries to apply the target language and results in several deviations on the target language (Rahimi & Tafazoli, 2014;Sawalmeh, 2013). The target language deviation is caused by incomplete learning, in which the students do not fully comprehend the target language construction (Guo, 2021;Rahman, 2019). Even though it is a common phenomenon, ignoring the errors may lead the students to perceive the error fossilization.…”
Section: Introductionmentioning
confidence: 99%
“…Profoundly, grammatical error investigations had been conducted. Some prior research has already revealed some types of errors that occur in students' writings, including in essays (Elmahdi, 2015;Pouladian et al, 2017), argumentative texts (Rahmatunisa, 2014), recount texts (Anggara & Haryudin, 2020), narrative texts (Kusumawardhani, 2015), synopsis (Rahman, 2019), and paragraphs (Al-khasawneh, 2014). However, based on these empirical studies, different types of writing carried out different types of errors.…”
Section: Introductionmentioning
confidence: 99%